2017
DOI: 10.1016/j.corsci.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Novel dual microelectrode probe for the simultaneous visualization of local Zn2+ and pH distributions in galvanic corrosion processes

Abstract: Novel dual potentiometric microsensor probe has been developed for the simultaneous detection of Zn 2+ concentration and pH distributions in the Scanning Electrochemical Microscopy investigation of corroding galvanized steel. The individual sensors show nearly theoretical behavior over a wide concentration range. The applicability of this probe is first demonstrated on a Fe-Zn galvanic couple, as it shows excellent performance in these simultaneous model experiments. In addition, linear scans recorded over a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The Pt electrode was used for amperometric detection of NO while the Ag electrode partially oxidized to AgCl and covered with K + -selective membrane served for potentiometric potassium detection. The dual sensor exhibited a close to Nernstian response slope (51.6 mV/dec) to K + from 10 -5 to 10 -1 M. The authors demonstrated the simultaneous monitoring of NO and K + in a living rat brain.Filotas et al reported on a dual potentiometric microsensor probe for the simultaneous detection of Zn 2+ and pH to study localized corrosion processes by Scanning Electrochemical Microscopy (SECM) 153. The dual sensor was fabricated using two intertwined borosilicate capillaries.…”
mentioning
confidence: 99%
“…The Pt electrode was used for amperometric detection of NO while the Ag electrode partially oxidized to AgCl and covered with K + -selective membrane served for potentiometric potassium detection. The dual sensor exhibited a close to Nernstian response slope (51.6 mV/dec) to K + from 10 -5 to 10 -1 M. The authors demonstrated the simultaneous monitoring of NO and K + in a living rat brain.Filotas et al reported on a dual potentiometric microsensor probe for the simultaneous detection of Zn 2+ and pH to study localized corrosion processes by Scanning Electrochemical Microscopy (SECM) 153. The dual sensor was fabricated using two intertwined borosilicate capillaries.…”
mentioning
confidence: 99%
“…In fact, multi-barrel electrode arrangements are often employed to perform physiological measurements [31][32][33][34][35], as to eliminate the effects of neural activity [36]. More recently, we introduced multi-barrel electrode probes in SECM measurements to either achieve combined amperometric/potentiometric operation [37], or to monitor the concentration distributions of various chemical species over an actively corroding system [38]. Therefore, simultaneous pH and Mg 2+ -ion concentration maps were recorded over a magnesium-iron galvanic pair [38].…”
Section: Introductionmentioning
confidence: 99%
“…Though quite good correlations have been attained from those separated measurements [33][34][35][36][37][38][39], the simultaneous monitoring of pH and zinc ion distributions in galvanic corrosion processes is desirable. Yet, due to the rather slow scanning rates required for imaging with ISME probes, the investigation of the dynamic corrosion reactions with high spatial resolution has been mostly based on the measurement of single scan lines instead [33][34][35][36], and recording of the actual 2D distribution maps could be scarcely attempted [40].…”
Section: Introductionmentioning
confidence: 99%
“…It consisted of a double barrel microelectrode probe that contained a Zn-ion selective and a pH-sensitive Sb-based microelectrodes sharing a common scanning tip. In this way, simultaneous recording of Zn-ion and pH concentration distributions were obtained for the first time, although the very slow scan rates imposed by the time constants of the microelectrodes prevented actual recording of 2D maps and the time evolution of a dynamic corrosion process had to be established from single line scans [40]. Simultaneously, new scanning algorithms and data evaluation methods allowing faster acquisition rates have been developed [45][46][47], and although they have only been tested for model current sources using noble metals, it is considered that it opens new possibilities for the in situ study of corrosion processes using potentiometric SECM.…”
Section: Introductionmentioning
confidence: 99%